Digital Humanities and Cyber-Feminism (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The field of digital humanities has been established on an assumption that we live in a world in which no one is the only producer, manager and disseminator of knowledge or culture. Universities are invited to form original digital models (web, blogospheres, digital libraries, etc.) and innovations in these areas. They ought to foster the establishment of a network for production, exchange and dissemination of knowledge. The openness of sources and access is the only principle. Digital humanities encompass: museums, libraries, archives, galleries without walls; democratization of knowledge and culture; the abolition of boundaries between natural and social sciences; intellectual creativity; mix of media; sometimes even digital anarchy and equal evaluation of creative copies and originals. In this article, author first describes advantages and limits of digital humanities, and then points to cyber-feminism, a feminist version of digital humanities, a new techno-culture, as well as opposition to patriarchal academic discourse.
Keywords: digital humanities; democratization of knowledge and culture; cyber-feminism